MEDIATING CUSTOMER SATISFACTION: THE IMPACT OF SERVICE QUALITY ON REPURCHASE INTENTION AT THE SURABAYA MUHAMMADIYAH UNIVERSITY SURYAMART RETAIL STORE - Farhan Arifirlana Akbar; Asyidatur Rosmaniar; Muhammad Alhakim Danurwindo; Muhammad Anang Firmansyah (International Conference on Economics, Management, Business, and Accounting, 2024)
This research was conducted to determine the influence of each variable service quality, repurchase intention and consumer satisfaction as intermediary variables. The population in this study were students, lecturers and local people who had made at least 1 purchase at the Suryamart retail store, University of Muhammadiyah, Surabaya. The sample chosen was based on a formula calculation of 60 respondents and the method used was a non-probability sampling technique (non-random sample) which means that each population has the same probability of being used as a sample or can also be called purposive sampling. Data calculations are carried out using the SmartPLS tool. The stages carried out are instrument testing, model measurement (outer model), model evaluation (inner model) and hypothesis testing. The results of the research show that the service quality variable has a positive and significant effect on the consumer satisfaction variable. The consumer satisfaction variable has a significant positive effect on repurchase intention. And, the service quality variable has a direct and significant effect on the repurchase intention variable through the consumer satisfaction variable. These results state that each variable has a positive and significant influence on other variables, because the P value is <0.05.